Levels of Self-Stigma and Resilience Among Single Working Parents Amidst the Pandemic in Barangay 176 Caloocan City: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In this pandemic, single working parents encountered different problems in terms of psychological, emotional, and physical. This research further explains self-stigma and resilience and discusses its harmful implications for single parents. It also examines the benefits and drawbacks of disclosure regarding reducing self-stigma and preserving resilience among working single parents. This study used a quantitative research approach, focusing on objective measurements and statistical, mathematical, or numerical analysis of data collected through polls, questionnaires, and surveys, as well as changing pre-existing statistical data using computing tools. This study used a Descriptive Correlational Research Design. The study's participants will be 100 single parents from Barangay 176 in Caloocan City. To assess the respondents' self-stigma and resilience, the researcher utilized the Self-stigma Test Scale (SST Scale) and Resilience Test Scale (ST Scale) questionnaires. The data implies that the single parents got a medium level of self-stigma and the highest level of resilience in terms of psychological, emotional, and physical amidst the pandemic at Caloocan City. The 100 respondents (N) computed .029 in Pearson correlation with 0.775 in two-tailed, and the null hypothesis was accepted.
Keywords: Self-stigma; Resilience; Single Parents; Psychological; Emotion; Physical; COVID-19 Pandemic